Management of End-stage Renal Disease Associated with Systemic Rheumatic Diseases - Honda, Suguru (JMA J, 2019)
The outcomes of rheumatic diseases (RDs) have improved over the past decades. However, a significant proportion of the patients still suffer from end-stage renal disease (ESRD) and have to bear the burden of hemodialysis. It is crucial to prevent patients with RDs from developing ESRD from viewpoints of medicine and medical economics. For those who already have ESRD, it is important to improve vial prognosis and quality of life through appropriate management of disease activity and comorbidities related to ESRD. Thus, rheumatologists and nephrologists need to recognize risk factors associated with progression to ESRD along with their appropriate management. Although the activity of most RDs tends to decrease after initiation of hemodialysis, disease activity may still increase, and recognizing how to appropriately use immunosuppressive agents even after the development of ESRD is crucial. The treatment of RDs needs extra attention as hydroxychloroquine requires more frequent monitoring for adverse drug reactions; therapeutic drug monitoring is necessary for mycophenolate mofetil, cyclosporine A, and tacrolimus; cyclophosphamide and azathioprine need dose adjustments; methotrexate and bucillamine are contraindicated in patients with ESRD; leflunomide and sulfasalazine do not require significant dose reduction and iguratimod should be carefully administered. The pharmacokinetics of biological agents such as rituximab or belimumab are not affected by ESRD, and dose adjustments are not necessary. Collaboration between rheumatologists and nephrologists is needed more than ever and is expected to produce a complementary effect and achieve better outcomes in clinical settings, although this cooperation has not always been conducted appropriately.